Drawing compared to writing in a diary enhances recall of autobiographical memories. Issue 3 (4th May 2023) - Tran, Sophia H. N.; Beech, Isaac; Fernandes, Myra A.
ABSTRACT: Drawing at encoding has been shown to improve later recall of to-be-remembered words, pictures, and academic terms, compared to when one simply writes out the target information. Here we examined whether drawing in a diary, compared to writing in it, differentially improved later memorability of personal autobiographical events, and whether aging influenced the magnitude of this effect. Thirty younger and thirty older adults were given a diary booklet, and instructed to use it to reminisce about a random daily event of their choosing, on 12 days within a two-week period. They recorded the event on each day in one of two ways, counterbalanced within-subject: by writing about or by drawing a picture of the event. Participants also generated a keyword descriptor for each event. After the two-week period, participants were cued using their keyword descriptors to recall each autobiographical memory by writing it down. Self-reported match accuracy, between reminisced and recalled events was tabulated. Across age groups, match accuracy was significantly higher for those drawn than written during the reminiscing phase. In addition, we compared the word count, level of detail, visual imagery, and point of view of the recalled memories. Self-reports of the level of detail in the recalled memory were better maintained for events drawn compared to written during the reminiscing stage, and better maintained in older than younger adults. Our findings suggest the use of drawing, while reminiscing within a diary format, enhances accuracy and quality of later recollections.